Examining the Effects of Familiness on the Capital Structure: the Case of French Family Firm (Journal of Legal Studies, 2022)
The aim of the article is to analyze the impact of the concept of familiness on the financing of French firms. In this respect, three factors are considered. The first one is about the presence of a family CEOs.The second deal with the presence of a family member and the third comes with transgenerational succession. Such an effect is highlighted by using a sample of 100 unlisted French family firms over the period 2003–2012. The results show that the involvement of the concept of "familiness" in family firms leads to a different financial structure from other firms. The ownership structure adopted by family CEOs and transgenerational succession improve debt. On the other hand, the presence of a family member on the board of directors does give significant results; the negative coefficients demonstrate reluctance regarding debt. A possible explanation for the paradox is that the capital structure of French family firms is specific.